How much information of concurrency can be got from firing sequences in Petri Nets - Ban, Doan Van; Hung, Dang Van (Journal of Computer Science and Cybernetics, 2016)
It is well know in [2, 3] that in general processes in Petri Nets are not recoverable from firing sequences. However, firing sequences in Petri Nets say something about concurrency. The paper presents a way to define concurrency form firing sequences of nets. It turns out that the information of concurrency in a firing sequence characterise all its processes.